Criminal Psychology: Investigative Techniques and Their Role in Modern Law Enforcement - Kamal Hasme; Eshan Singhal (International Journal of Indian Psychȯlogy, 2025)
Criminal psychology is the sphere of activity joining psychology and law, the knowledge of which enables one to take into account the offender’s behavior and assist the investigative efforts. This paper discusses some core investigative methods-psychological profiling, behavioral analysis, cognitive interviewing, and psychophysiology-and discusses how these investigative tools are put into practice, their effectiveness, and their ethical implications. By examining both the historical and state-of-the-art developments, this research puts special emphasis on the interdisciplinary relationship between psychology and the police. The case studies and methodological critiques bring into focus the refinement in these techniques, necessary for justice and also to prevent recidivism. The findings point out the need for increased training and integration of psychological expertise in dealing with crime.